Darwin’s forgotten weevil - Oberprieler, Rolf G.; Thompson, Richard T.; Peterson, Magnus (Zootaxa, 2010)
G. R. Waterhouse (1839) described the first species of weevil from the specimens collected by Charles Darwin in Australia in 1836. Named Belus testaceus, it was subsequently forgotten in all literature on Australian Belidae. Study of the type, as preserved in the Natural History Museum, London, revealed its name to be a senior synonym of Belus linearis Pascoe, 1870 (syn. n.). Known from only another six specimens taken about a century ago at the same locality, King George Sound (present-day Albany) in Western Australia, plus another four of uncertain origin, this species, now in the genus Stenobelus Zimmerman, appears to be restricted to the southern tip of Western Australia but of unknown current distribution, if it is indeed still extant. The only other species of the genus, S. tibialis (Blackburn), has a wider but highly fragmented distribution across Australia, apparently being common only in the acid swamplands (wallum) of south-eastern Queensland. The larval hostplants of both species are unknown. Diagnoses are provided for the genus Stenobelus as well as for its two species, and the holotypes of all applicable names are illustrated, together with the diagnostic features of the genus. Six species recently transferred to Stenobelus from Rhinotia by Legalov (2009) are again excluded from this genus, and the name of the subgenus Germaribelus Legalov, 2009 is placed in synonymy with Rhinotia Kirby, 1819 (syn. n.).